Cervical Lymph Node Sarcoidosis Mimicking a Parathyroid Adenoma: A Clinical Case. Issue 6 (January 2013) - Calò, Pietro Giorgio; Pisano, Giuseppe; Tatti, Alberto; Loi, Giulia; Furcas, Silvia; Nicolosi, Angelo
We report a case of cervical lymph node sarcoidosis misdiagnosed as parathyroid adenoma. This is the second case described in the literature in which lymph node sarcoidosis was misdiagnosed as parathyroid adenoma on Tc-99m sestamibi (MIBI) scan, the first case localized in the neck. A 64-year-old woman presented with a hypercalcemia. Neck ultrasonography revealed a paratracheal hypoechoic mass of 15 mm with peripheral vascularization. MIBI scan and SPECT/CT identified a MIBI-positive area corresponding to the nodule detected by ultrasonography suggestive for a lower right parathyroid adenoma. A mass interpreted as the lower parathyroid was excised associated to a total thyroidectomy. Pathologic examination revealed a granulomatous lymph node consistent with active sarcoidosis. Sarcoidosis should be suspected as a cause of unexplained hypercalcemia and the differential diagnosis of hypercalcemia, even in presence of MIBI uptake, must include sarcoidosis localized in an isolated cervical lymph node.